Vascular Calcification in Diabetic Kidney Disease - Olivier Phan; Nobuhiko Joki (MDPI AG, 2022)
The pathogenesis of vascular calcification (VC) in diabetes mellitus (DM) has not been completely elucidated. VC often occur in patients with DM and chronic kidney disease (CKD). The incidence of VC in diabetic patients is more frequent than in nondiabetic patients, which is an important cause of cardiovascular (CV) morbidity and mortality. VC is a progressive transformation of the vascular wall; it results from an active and complex phenomenon affecting particularly the vascular smooth muscle cells (VSMCs). It leads to a change in the phenotype of the VSMCs towards an osteoblastic-like phenotype. DM is associated with specific risk factors in addition to hyperglycemia, such as increased oxidative stress, proinflammatory state, hypertension, and chronic kidney disease (CKD) promoting endothelial dysfunction. This article provides an overview and update of the pathophysiological data on the role of DM in VC progression.